Needs Analysis in an English for Legal Purposes Context: A Case Study of Serbian Law Professionals - Gajić, Tijana D. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
Teachers of English for Specific Purposes (ESP) often employ needs analysis to identify their students’ most important needs and skill gaps. The focus of this study is on the needs and preferences of legal experts in the Republic of Serbia. The study presents findings from an online survey of 101 law professionals aimed at identifying their learning needs, pinpointing key English for Legal Purposes (ELP) skill gaps, examining their attitudes towards ELP, evaluating the significance of English language study during legal education, and providing recommendations on integrating ELP into legal education, emphasizing practical scenarios relevant to the Serbian legal context. Given the multilingual nature of the EU, which Serbia aspires to join, it is essential to equip law students and legal professionals with the interdisciplinary knowledge and language skills necessary for the evolving job market. The importance of ESP for the legal profession is one of the main reasons for determining how familiar legal professionals are with it and their perspectives on the significance of learning the English language within the legal field. The respondents believe that learning ELP should be based on acquiring legal terminology and simulating real-life situations from law firms, courtrooms, business discussions, and circumstances within the Republic of Serbia, rather than reading and analyzing texts about legal practices in England or the USA. The study’s findings highlight specific areas that need special emphasis when honing Legal English proficiency: public speaking, vocabulary development, legal writing, and telephone communication.
Keywords: needs analysis; English for Legal Purposes (ELP); English for Specific Purposes (ESP); law practitioners